Pengaruh Pendapatan, Rumah Kosong, dan Pelanggan Merasa Tidak Menggunakan terhadap Piutang Tertunggak pada PT. Telkom Cabang Kendari - Nurwati, Nurwati (Jurnal Aplikasi Manajemen, 2009)
As for purpose of which wish to be reached in this research is: "to know earnings, empty home, and cutomer feels not to apply having an effect on to receivables delayed payment at PT TELKOM cabang Kendari". Analyzer applied is doubled linear regression to know earnings influence, empty home and cutomer feels not to apply to receivables delayed payment at PT TELKOM cabang Kendari. Result of research with multiple regression test obtained that in together earnings variable, empty home and cutomer doesn't feel applies influential significant to receivables is delayed payment, hence thereby hypothesis submitted in this acceptable research of its (the truth or hypothesis received).